Effects of flow rates and composition of the filter, and decay/ingrowth correction factors involved with the determination of in situ particulate 210Po and 210Pb in seawater. (8th January 2013) - Baskaran, Mark; Church, Thomas; Hong, Gi; Kumar, Anupam; Qiang, Ma; Choi, Hiu; Rigaud, Sylvain; Maiti, Kanchan
<x xml:space="preserve">Abstract</x> Accurate measurements of particulate 210Po (210Pop) and 210Pb (210Pbp) are required in the investigation of (i) partitioning of Po and Pb between particulate and dissolved phases and (ii) export estimates of carbon and other key trace metals from the euphotic zone via sinking particulate matter. Based on the intercomparison of different composition of the filter material (QMA, Supor, Millipore, and Pall GN6) and flow rates (2 to 8 L min), we show how these factors affect the measured concentrations of 210Pop and 210Pbp and their activity ratios (AR). As such, we recommend using Supor 0.4 µm filter and a flow rate of up to 8 L/min for the measurements of 210Pop and 210Pbp. Furthermore, we inter‐compared 210Pop and 210Pbp obtained by small‐volume McLane and large‐volume MULVFS pumps. The activities of 210Pop in MULVFS filter samples are somewhat higher than that of McLane filter samples, whereas the 210Po/210Pb AR collected by McLane pump is distinctly lower, suggesting some fractionation in the collection process by the pumping systems. Likewise comparison of vertical profiles of 210Pop and 210Pbp obtained using McLane pumps by two independent research groups at the two intercalibration stations in the Pacific Ocean show quite similar values except in the mesopelagic waters, suggesting possible uneven loading and presence of larger gelatinous plankton in the filter. Finally, we append a detailed analysis of various correction factors for the accurate calculation of in situ 210Po and 210Pb. Presented results are relevant to the worldwide community that uses 210Po‐210Pb as tracers in aquatic systems.